The Potentials of Limau (Citrus amblycarpa Hassk. Ochse) as A Functional Food and Ornamental Mini Tree Based on Metabolomic and Morphological Approaches - Budiarto, Rahmat; Poerwanto, Roedhy; Santosa, Edi; Efendi, Darda (Journal of Tropical Crop Science, 2017)
Limau (Citrus amblycarpa (Hassk.) Ochse) is one of the native Citrus species of West Java that is grown in the local backyard, thus is easily found in local cuisines. Limau has great potentials for use as a potted plant in home gardens for its aesthetic value and fragrance. The objective of this research was to describe the metabolites fingerprint and morphology of Limau as a potential functional and ornamental mini tree. Methanol leaf extracts from one-year-old Limau originated from Bogor were analyzed using untargeted Gas Chromatography Mass Spectrometry (GCMS). Methanol leaf extract was dominated by vitamin E and composed of other 18 metabolites including phytosterols, fatty acids and terpenes. The major portion of fruit extract consisted of 6-octadecenoic acid, palmitate and various fragrance compounds such as alpha sinensal, alpha limonene, beta citronellal, citronellol, and sabinene. Limau fruits are also a functional food due to its rich antioxidant and aromatic content in the fruits. The morphology of limau tree is suitable as a potted ornamentals or mini-fruits tree for its small crown, sparse branching with unifoliate aromatic leaves and small spines, and plentiful aromatics mini fruits with the diameter of around 2-4 cm.